FBXO22, an epigenetic multiplayer coordinating senescence, hormone signaling, and metastasis. Issue 8 (17th July 2020) - Johmura, Yoshikazu; Harris, Alexander S.; Ohta, Tomohiko; Nakanishi, Makoto
Abstract: Ubiquitin‐dependent protein degradation has been implicated in the control of various cellular processes such as cell cycle control, transcriptional regulation, DNA damage repair, and apoptosis, many of which are involved in the initiation, progression, metastasis, and drug resistance of cancers. E3 ubiquitin ligases are known to be the second most prevalent cancer‐related functional gene family next to protein kinases. Of these, FBXO22, an F‐box receptor subunit of SCF E3 ligase, has recently been proposed to play a critical role in multiple aspects related to cancer development and therapy response. Firstly, FBXO22 is a key regulator of senescence induction through ubiquitylation of p53 for degradation. FBXO22 also acts as a molecular switch for the antagonistic and agonistic actions of selective estrogen receptor modulators (SERM) and determines the sensitivity of breast cancer to SERM by ubiquitylating KDM4B complexed with unliganded or SERMs‐bound estrogen receptor (ER). Furthermore, FBXO22 binds to Bach1, a pro‐metastatic transcription factor, suppressing Bach1‐driven metastasis of lung adenocarcinoma, and loss of FBXO22 facilitates metastasis. These findings, as well as other reports, unveiled strikingly important roles of FBXO22 in cancer development and therapeutic strategy. In this review, we summarize recent findings of how FBXO22 regulates major cancer suppression pathways. Abstract : Fbxo22 plays strikingly important roles in cancer development and therapeutic strategy through the regulation of p53, KDM4B, and Bach1.